Canada : Financial Sector Assessment Program; Detailed Assessment of Observance of the CPSS/IOSCO Recommendations for Securities Settlement Systems. (IMF Staff Country Reports; Country Report ;, 2008)
The Canadian Depository for Securities (CDS) is the operator of the securities settlement system. The design and operations of the CDS are covered by a solid legal basis. The regulatory framework is clear and transparent to market participants. The risk management procedures of the CDS as a Central Counterparty (CCP) have not yet been assessed against the Committee on Payments and Settlements Systems Recommendations for CCP. The CDS should explicitly assess the benefits and costs of acting as a CCP for trade-for-trade (TFT) transactions.